2006
DOI: 10.1002/qua.20980
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effect on geometry and nonlinear optical response of conjugated organic molecules

Abstract: ABSTRACT:In this paper the effect of solvents of different polarity (chloroform and acetone) on the geometry and static electric properties (dipole moment, polarizability, and first hyperpolarizability) of four nonlinear optical (NLO) chromophores is studied within the framework of the Polarizable Continuum Model (PCM) at the Self-consistent Field (SCF) level. The standard 6-31G** basis set is used for the chromophore geometry optimization both in the gas phase and in the solvents, and a moderate-size aug-cc-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 41 publications
6
19
0
Order By: Relevance
“…43 The differences between experimental and calculated values are within 6%, a good result given that calculations do not account for wavelength dispersion or solvent effects. 44,45 Our results are also in good agreement with other additive models of dipole polarizabilities. 46 The isotropic polarizabilities computed via the transferable groups (shown in Table 2 In order to confirm the validity of the transferable functional groups, we computed the polarizability of some molecules, for example -alanine and -aminoisobutyric acid, that contain the same functional groups but that are outside the set used to construct the database.…”
Section: Atomic and Functional Group Polarizabilities In Amino Acid Msupporting
confidence: 89%
“…43 The differences between experimental and calculated values are within 6%, a good result given that calculations do not account for wavelength dispersion or solvent effects. 44,45 Our results are also in good agreement with other additive models of dipole polarizabilities. 46 The isotropic polarizabilities computed via the transferable groups (shown in Table 2 In order to confirm the validity of the transferable functional groups, we computed the polarizability of some molecules, for example -alanine and -aminoisobutyric acid, that contain the same functional groups but that are outside the set used to construct the database.…”
Section: Atomic and Functional Group Polarizabilities In Amino Acid Msupporting
confidence: 89%
“…For example, Balakina and coworkers [29,31], studied theoretically a series of non-linear optical chromophores and demonstrated that the formation of weak to moderate N-H⋅⋅⋅O bonds (with donor-acceptor Figure 2. Distributed atomic polarizability ellipsoids of a p-nitroaniline dimer extracted from the crystal structure, calculated at the CAM-B3LYP/cc-pVDZ level of theory.…”
Section: Figurementioning
confidence: 99%
“…This means that these interactions may be useful for controlling the anisotropy of crystalline optical properties, The cluster approach has been previously used to investigate the effect of hydrogen-bond formation on the (hyper)polarizabilities of a few other organic materials. For example, Balakina and coworkers [29,31], studied theoretically a series of non-linear optical chromophores and demonstrated that the formation of weak to moderate N-H¨¨¨O bonds (with donor-acceptor distances in the range 2.8-3.5 Å) results in an increment of only 10%-15% of the molecular polarizability α, whereas the first hyperpolarizability β may increase up to three times. It is anyway noteworthy that even small changes in α will significantly affect the calculation of the electric susceptibility through a lattice summation.…”
Section: Figurementioning
confidence: 99%
“…2 Furthermore, their optical properties in solvent environments are sensitive to the nature of the solvent and solute-solvent interactions, [3][4][5] which can be quite complex, involving hydrogen-bonding and long-range screening. To capture the effects of solvents on the optical properties of solutes, the DFT based EFP1 model ͑EFP1/DFT͒ 11 was employed.…”
Section: Computational Approachmentioning
confidence: 99%